EDUKASI STUNTING DENGAN PENDEKATAN FOCUS GROUP DISCUSSION (FGD) DAN PELATIHAN PEMANTAUAN PERTUMBUHAN BALITA SECARA MANDIRI OLEH ORANG TUA - Petrika, Yanuarti; Desi, Desi; Dewintha, Rezza; Melyana, Yola Putri; Hapisa, Tiara; Wulandari, Devi Nur (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2023)
Stunting is an indication of poor nutritional status and is used as a long-term indicator of malnutrition in children. Determining stunted toddlers generally begins by taking anthropometric measurements in the form of the toddler's height and is carried out by health officers or cadres at Posyandu. In fact, the role of parents is very important, even as the front guard in monitoring children's growth. The problem is that people feel they are only objects or targets of programs that are continuously given education without being given the opportunity to become subjects, for example by being given skills. The aim of implementing the community service is to improve the skills of mothers of toddlers in measuring the height of toddlers, improve the skills of mothers of toddlers in monitoring the nutritional status of toddlers independently and increase the knowledge of mothers of toddlers regarding stunting and appropriate eating behavior for toddlers which supports the growth of toddlers. The methods of community service activities that will be carried out include providing training on anthropometric measurements of toddlers' height, monitoring the nutritional status of toddlers independently and education using an FGD approach to mothers of toddlers. The results for this community service show that respondents took more measurements according to the sequence and more respondents took measurements according to the KMS filling procedure. There was an increase in the knowledge of mothers of toddlers after being given 20 points of education. Apart from that, based on the results of statistical tests, it shows that there is a difference in knowledge before and after being given education (p=0.00). It is necessary to carry out monitoring and evaluation of mothers of toddlers by Posyandu cadres in terms of measuring and monitoring the growth of their toddlers. If necessary, you can involve a nutrition lecturer as a companion every 3 months, especially in measuring the height of toddlers.